2023
DOI: 10.3390/pharmaceutics15020449
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-NSAIDs Molecular Salts: A Path towards Enhanced Oral Bioavailability and Stability

Abstract: According to the World Health Organization, more than 422 million people worldwide have diabetes. The most common oral treatment for type 2 diabetes is the drug metformin (MTF), which is usually formulated as a hydrochloride to achieve higher water solubility. However, this drug is also highly hygroscopic, thus showing stability problems. Another kind of worldwide prescribed drug is the non-steroidal anti-inflammatory drug (NSAID). These latter, on the contrary, show a low solubility profile; therefore, they m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, MET has no hypoglycemic effect on normal people [ 16 ]. Metformin–hydrochloride (MET-HCl), chemically defined as a salt to enhance solubility and stability, is the most commonly prescribed formulation [ 17 ]. Clinical trial data have demonstrated that MET is safe for most individuals and unsafe for patients with severe hepatic, cardiac, or renal insufficiency [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MET has no hypoglycemic effect on normal people [ 16 ]. Metformin–hydrochloride (MET-HCl), chemically defined as a salt to enhance solubility and stability, is the most commonly prescribed formulation [ 17 ]. Clinical trial data have demonstrated that MET is safe for most individuals and unsafe for patients with severe hepatic, cardiac, or renal insufficiency [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hope to use the excellent solubility of MET to improve the solubility and bio-absorption of NSAIDs. Diclofenac, niflumic acid, diflunisal, mefenamic acid, tolfenamic acid, and flurbiprofen are NSAIDs reported as salts with metformin [ 17 , 26 ]. These salts increased the solubility of NSAIDs; however, none were subjected to systematic pharmacokinetic experiments to evaluate their biological activity.…”
Section: Introductionmentioning
confidence: 99%